Malignant Germ cell Tumor of Ovary: An Unusual Combination and An Irony of Fate - Sutradhar, Arpita; Khan, Enam Murshed; Gupta, Shaikat; Maitra, Sudipta Kumar; Ghosh, Somdeep (Annals of Pathology and Laboratory Medicine, 2021)
Malignant mixed ovarian germ cell tumors are very rare malignant ovarian germ cell tumors, with a very high degree of malignancy. They are aggressive cancers affecting young adolescent girls. The commonest combination reported in literature is dysgerminoma and endodermal sinus tumors. Fertility sparing surgery followed by combination chemotherapy is the treatment of choice. The objectives of this case report are the advanced age of presentation, unusual histopathological combination, and the irony of infertility treatment. We report a rare case of 40-year-old woman with Malignant mixed germ cell tumor comprising of components of endodermal sinus tumor, immature teratoma, dysgerminoma and embryonal carcinoma. Patient was on hormonal therapy for the cause of infertility, presented with complains of lower abdominal pain, constipation and incomplete evacuation of bladder for 2months. Transvaginal ultrasonography and CT scan showed a large multicystic space occupying lesion with predominant solid component in midline abdominopelvic location. Tumor markers i.e., AFP, Prolactin and CA125 were raised. Total abdominal hysterectomy and bilateral salpingoophorectomy, pelvic and retroperitoneal node resection, peritonectomy and omentectomy was performed.